How self‐compassion moderates the effect of body surveillance on subjective happiness and depression among women. Issue 5 (31st May 2019) - Wollast, Robin; Riemer, Abigail R.; Bernard, Philippe; Leys, Christophe; Kotsou, Ilios; Klein, Olivier
Abstract : According to objectification theory (Fredrickson & Roberts, 1997), being treated as an object leads women to engage in self‐objectification, which in turn increases body surveillance and body shame as well as impairs mental health. However, very little is known about what factors could act as buffers against the detrimental consequences of self‐objectification. This paper seeks to understand the role of self‐compassion (the ability to kindly accept oneself or show self‐directed kindness while suffering) in the perception that women have of their own bodies. Results indicate that self‐compassion moderated the effect of body surveillance on depression and happiness separately among women. More specifically, for women low in self‐compassion, body surveillance was negatively associated with happiness, which was explained by increased depression. In sum, our results indicate that self‐compassion protects against the detrimental consequences of body surveillance.